1998
DOI: 10.1039/a804700f
|View full text |Cite
|
Sign up to set email alerts
|

Quantification of total chromium and hexavalent chromium in UHT milk by ETAAS

Abstract: Procedures for the quantification of total chromium and hexavalent chromium in UHT milk samples are presented. Total chromium was determined directly in milk with the addition of a surfactant and a mixture of Pd and Mg as a chemical modifier. For the selective separation of hexavalent chromium, the sample pre-treatment consisted in precipitation of proteins and elution of the supernatant through a Chromabond NH2 column. The metal was eluted with nitric acid. Both total chromium and hexavalent chromium were eva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
1
1

Year Published

2000
2000
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 21 publications
1
23
1
1
Order By: Relevance
“…Lameiras et al 22 reported detection limits of 0.20 and 0.15 for total Cr and Cr(VI), respectively, in their studies of chromium speciation in UHT milk using ETAAS. These values are 2.20 and 1.76 times higher than the detection limits found for the method currently proposed.…”
Section: Limits Of Detection (Lod)mentioning
confidence: 99%
See 2 more Smart Citations
“…Lameiras et al 22 reported detection limits of 0.20 and 0.15 for total Cr and Cr(VI), respectively, in their studies of chromium speciation in UHT milk using ETAAS. These values are 2.20 and 1.76 times higher than the detection limits found for the method currently proposed.…”
Section: Limits Of Detection (Lod)mentioning
confidence: 99%
“…For proper comparison of the total Cr level with Cr(VI), the total Cr level in all freeze-dried milk samples, given by ng/g dry mass, were converted to mg/L ( Table 3). Considering that the solid extract of raw milk is 130 g/L, 22 and after converting the results into mg/L, levels ranging from 33.2 to 57.1 mg/L were found for total Cr. On the basis of these results, milk samples contained 1.31 to 3.28% Cr(VI).…”
Section: Concentrations Of Cr(vi) and Total Cr In Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Entre os trabalhos encontrados na literatura sobre determinação de metais em açúcar, a maioria utiliza AAS, preferencialmente com atomização eletrotérmica em forno de grafite. 18 quantificaram o teor de Cr (VI) e Cr total em leite por atomização eletrotérmica em forno de grafite. O Cr total foi determinado em leite através da adição de Triton X-100 e uma mistura de Pd e Mg utilizado como modificador químico.…”
unclassified
“…The application tested here is the NH 2 column method, which selectively sorbed Cr(VI) while Cr(III) remains unsorbed. Originally, it was developed to determine Cr(VI) levels in infant milk products by Lameiras et al (1998) and Soares et al (2000). They found that the method was precise and accurate with good sensitivity for low Cr(VI) concentration.…”
Section: Introductionmentioning
confidence: 99%